A Study of Reverse Characteristics of GaN-on-Si Quasi-Vertical PiN Diode with Beveled Sidewall and Fluorine Plasma Treatment - Fuchun Jia; Qingyuan Chang; Mengdi Li; Yungang Liu; Ziyan Lu; Jifan Zhang; Jinming Lai; Hao Lu; Yang Lu; Bin Hou; Ling Yang; Xiaohua Ma (Micromachines)
In this work, we show a high-performance GaN-on-Si quasi-vertical PiN diode based on the combination of beveled sidewall and fluorine plasma treatment (BSFP) by an inductively coupled plasma (ICP) system. The leakage current and breakdown voltage of the diode are systematically studied. Due to the beveled sidewall treated by the fluorine plasma, the diodes achieve an excellent breakdown voltage (VBR) of 790 V and a low reverse leakage current. In addition, the GaN-on-Si quasi-vertical PiN diode achieves a low specific on-resistance (Ron,sp) of 0.51 mΩ·cm2 and a high Baliga’s figure of merit (BFOM) of 1.22 GW/cm2. The relationship between the total leakage current and the device diameter shows that the sidewall leakage is the main leakage path of the device. Afterwards, the TCAD simulations based on electric field and electric potential reveal that the fluorine plasma treatment is a major factor in suppressing the leakage current and increasing the VBR for a diode with BSFP. This work systematically analyzes the effects of beveled sidewall and fluorine plasma treatment based on the reverse characteristics of the GaN-on-Si quasi-vertical PiN diode and highlights the great potential of the GaN-on-Si PiN diode for various power applications.